Educação do campo, identidade de jovens camponeses e tecnologias : contradições e desafios - Moura, Josivan dos Santos (2022)
This research aimed to understand the extent to which Information and Communication Technologies (ICT) contributed to the formation of the peasant identity of high school students at the Nossa Senhora Santana State School, located in the Santana dos Frades settlement in the municipality of Pacatuba-SE. To carry out the research, we used Dialectical Historical Materialism as a method of interpretation and understanding of the investigated object because we believe that the Marxist dialectic is part of the construct of the production of valid knowledge capable of showing the nature of the contradictions imposed on society. We used as main theorists: Marx (1975, 2011), Engels (1970, 1980, 2008), Hall (2019), Bogo (2010), Almeida (2020), Caldart (2011), Molina (2011). We had as subjects of the research the students and teachers of the High School of the mentioned school, however the centrality of the investigation were the students. We used the questionnaire with the students and the semi-structured interview in the data collection, both subjects participated. The peasant territories in Sergipe need to stay alive, consequently, they need the “strength” of the peasant youth, but this does not happen with the participation of the students investigated in the Santana dos Frades settlement. This reality is deeper than we imagined to find in the empirical field of research. It is a condition that permeates the power of the landowners, agribusiness and the silencing of the State acting as “leeches” in the territory of the settlement field. Thus, students face, in their daily lives, the dilemmas that torment them without necessarily thinking about the possibility of overcoming them. After the end of the research, we managed to establish some answers, even if they are not unique and definitive: a) the students of Escola Santana are living in a political and contradictory reality whose historical heritage in Sergipe proclaims the countryside as a backward, inferior and incapable territory; b) the conditions imposed on students try to deterritorialize, control, exploit and decriminalize them. This was perceived through the contradictions that we identified during the research. The presence of peasant identity internalized in the praxis of these students is a major condition for the process of reversal of this capitalist logic, given that peasant identity is linked to peasant struggles, to class struggle, to the struggle against oppression, to the struggle for equality of rights and the fight for social and material opportunities.However, if, on the one hand, such an identity is the driving force that can guide and motivate them to seek a new reality for the situation of the peasantry in the territory of the Santana dos Frades field, on the other hand, the ICTs identified and confirmed in the daily lives of these young students do not contribute to the formation of peasant identity, at least for the time being. In the way they are appropriated and used by students, ICT fully reflect the purposes of capital; laden with logic contrary to the peasant's revolutionary thinking. They are “encapsulated” technologies of market-oriented capitalist interests. In this way, everything that we investigated and that it was possible to detect and record is part of a complex situation that imposes on these students to face, day after day, the difficulties experienced in the settlement in order to rebuild, in the midst of disputes and struggles, the perspectives of a better future life.